The petrology and geochemistry of the Água de Pau Volcano, São Miguel, Azores - Marriner, Giselle Frances (1982)
During recent years several geochemical investigations have centred upon the Azores (Schmincke 1973, Schmincke and Weibel 1973, Flower et al., 1976, White et al., 1979) with particular emphasis being laid upon inter island differences. Islands have been characterised as being relatively potassic (São Miguel) less potassic (Flores and Santa Maria) and sodic (Pico, Fayal, São Jorge, Graciosa and Terceira) (Flower et al., 1976). However, several of these islands are complex, consisting of several centres displaying multiple compositional trends. In this study we have concentrated upon lavas erupted from one volcano, that of Agua de Pau on the island of São Miguel. The volcano consists of a central cone from whose caldera explosive trachytic eruptions have taken place. Basic and intermediate subsidiary cones are situated on its flanks, which have produced both lava flows and pyroclastics (Booth et al., 1978).